WHAT IS ECONOMICS? AN EXPLORATION OF THE FUNDAMENTAL CONCEPTS AND PRINCIPLES ("Conference on Universal Science Research 2023", 2023)
This scientific article provides a comprehensive analysis of the discipline of economics, aiming to answer the fundamental question: What is economics? We delve into the core concepts, theories, and principles that underpin the field of economics, its significance in understanding human behavior and resource allocation, and the impact of economic decisions on societies and individuals. By examining the history and evolution of economic thought, we offer a multi-dimensional perspective on economics as both a social science and a policy tool.